Nitrogen and Phosphorus Removal in a Rain Garden Flooded with Wastewater and Simulated Stormwater. Issue 2 (December 2015) - Strong, Patrick; Hudak, Paul F.
Abstract : Rain gardens, also known as bioretention cells, are low‐impact developments designed to mitigate several problems associated with urban stormwater. This four‐month field study involved a rain garden at a wastewater treatment plant in north‐central Texas in the United States of America. Partially treated wastewater from an anaerobic digester spilled into the rain garden at the beginning of the study. Subsequently, inflow and outflow concentrations of nitrogen and phosphorus were measured for nine simulated floods, preceded by dry‐spell intervals of 5, 8, or 12 days. Despite large inputs from the wastewater spill, the rain garden gradually processed and flushed the nitrogen. Longer dry spells tended to produce relatively higher outflow nitrate concentrations. A large pool of phosphorus in the soil restricted the rain garden's ability to reduce outflow orthophosphate concentrations, which were stable and lower than inflow concentrations throughout the study; however, adsorptive processes attenuated a relatively high inflow concentration by the end of the study.